A Suitable Occlusion - McCoy, Gene (British Journal of Healthcare and Medical Research, 2024)
Recently, an article1 appeared asking, what is the most suitable occlusion for implant rehabilitation? The question is challenging since we have yet to answer that question for ordinary restorative dentistry. Occlusion has the reputation of being the most crucial subject in dentistry, but also the most controversial. After all these years, what seems to be the problem? Exactly, what is a suitable occlusion? A simple answer is evasive because, over the years, the word’s meaning has changed from an adjective describing teeth closure to a noun understanding of the masticatory system itself.2 The circumstances that led to this transformation began when dentists were confronted with the damaging lateral forces of bruxism. They focused solely on the management because there was insufficient information regarding bruxism’s etiology to assume a proactive approach. They discovered that by equilibration, bruxism’s destructive lateral forces could be reduced by redirecting them to a more forward position (group function to cuspid rise). Since this process of “creating an occlusal scheme” successfully reduced heavy lateral forces, it became apparent that occlusion in function was just as important, maybe more so, than occlusion in closure, and the term “Functional Occlusion” 3became synonymous with the masticatory system.